Hadis pada Masa Pembaharuan Islam di Minangkabau: Telaah Penggunaan Hadis Dalam Majalah Alchoethbah karya Hs. Moenaaf - Saputra, Doni; Rafika, Alfiah; Yasti, Suci Amalia (UIN Sultan Syarif Kasim Riau, 2024)
The issue of Islamic reform in Minangkabau during the twentieth century was closely linked to the development of literacy and the culture of writing. The expansion of literacy during this period served as a crucial reference point for the public’s engagement with Islam, particularly through periodicals. This article seeks to analyze the use of hadiths in Alchoethbah magazine, which was published in Minangkabau in the early twentieth century. The hadiths examined address themes such as the prohibition of prioritizing reason over religious law thereby deviating from Islamic teachings and the significance of unity. These themes were employed by Hs. Moenaaf as forms of legal and moral legitimation in his writings. Employing a qualitative research methodology, this study analyzes various library sources with a focus on the hadiths cited in Alchoethbah magazine. The collected data were critically examined through a narrative analysis approach. The findings indicate that two specific hadiths were utilized and authored by Hs. Moenaaf in Alchoethbah to advance ideas of Islamic reform within his sermon-like narratives. Broadly, these hadiths were contextually pertinent to the reformist movement of the time for two primary reasons. First, Hs. Moenaaf, as both a scholar and writer, was part of the Kaum Mudo intellectual movement, which emphasized adherence to Sharia over reason and custom. Second, Alchoethbah functioned as a medium to facilitate readers’ understanding of the teachings of Islamic reformist scholars, particularly the injunctions against prioritizing reason over the Sharia of the Prophet Muhammad and against division or sectarian fanaticism within the Muslim community.Abstrak: Isu pembaharuan Islam di Minangkabau pada abad ke-20 kental dengan kemajuan literasi tulis-menulis. Kemajuan literasi pada periode ini dijadikan sebagai bahan referensi masyarakat untuk mempelajari Islam, salah satunya melalui majalah. Artikel ini bertujuan untuk mengungkap pengunaan hadis dalam majalah Alchoethbah yang terbit di Minangkabau awal abad 20. Penggunaan hadis yang dimaksud meliputi tema larangan mengedepankan akal dibanding syariat (menyelisihi ajaran agama) dan pentingnya rasa persatuan. Kedua tema hadis tersebut digunakan oleh Hs. Moenaaf sebagai bahan legitimasi hukum dalam tulisan-tulisannya. Penelitian menggunakan metode penelitian kualitatif dengan menganalisis sumber-sumber pustaka. Penelitian ini fokus pada hadis-hadis yang dikutip dalam majalah Alchoetbah, data-data yang diperoleh kemudian dianalisis secara kritis dengan metode analisis naratif. Hasil analisis menemukan bahwa terdapat dua hadis yang digunakan dan ditulis oleh Hs. Moenaaf di dalam majalah Alchoetbah untuk megusung ide-ide pembaharuan Islam dalam narasi khotbahnya. Secara garis besar hadis-hadis ini relevan penggunaannya pada masa pembaharuan Islam, setidaknya ada dua argumen yang menjadi landasannya. Pertama, Hs Moenaaf selaku penulis merupakan bagian dari intelektual dan ulama Kaum Mudo yang mendorong untuk lebih mengedepankan syariat dibandingkan akal dan tradisi. Kedua, Alchoethbah hadir sebagai salah satu media untuk memudahkan dalam memahami ajaran para ulama pembaharu Islam, seperti larangan mengedepankan akal dan lebih mendahulukan syariat Nabi Muhammad Saw serta larangan dalam berpecah-belah dan fanatisme kelompok.